Germination variation in Arabidopsis thaliana accessions under moderate osmotic and salt stresses - Vallejo, Augusto Julian (2010)
BACKGROUND: Water and salt stresses are two important environmental factors that limit the germination of seeds in most ecological environments. Most studies conducted so far to address the genetic basis of the above phenomenon have used stress conditions that are much more extreme than those found in natural environments. Furthermore, although an excess of ions and water restrictions have similar osmotic effects on germination, the common and divergent signalling components mediating the effects of both factors remain unknown. METHODS: The germination of seeds was compared under solutions of NaCl (50 mm) and polyethylene glycol (PEG, -0·6 MPa), that establish mild stress conditions, in 28 Arabidopsis thaliana accessions. Because Bayreuth (Bay) and Shadara (Sha) accessions showed contrasting sensitivity responses to both stresses, a quantitative trait locus (QTL) analysis was carried out using Bay × Sha recombinant inbred lines (RILs) to identify loci involved in the control of germination under mild salt and osmotic stresses. KEY RESULTS: Two loci associated with the salt sensitivity response, named SSR1 and SSR2 QTLs, and four loci for the osmotic sensitivity response, named OSR1-OSR4 QTLs, were mapped. The effects of the SSR1 QTL on toxic salt sensitivity, and the osmotic contribution of OSR1, were confirmed by heterogeneous inbred families (HIFs). Whilst the SSR1 QTL had a significant effect under a wide range of NaCl concentrations, the OSR1 QTL was confirmed only under moderate drought stress. Interestingly the OSR1 QTL also showed pleiotropic effects on biomass accumulation in response to water deficit. CONCLUSIONS: The regulation of germination under moderate salt and osmotic stresses involves the action of independent major loci, revealing the existence of loci specifically associated with the toxic component of salt and not just its osmotic effect. Furthermore, this work demonstrates that novel loci control germination under osmotic stress conditions simulating more realistic ecological environments as found by populations of seeds in nature.